High-Resolution FBG-Based Fiber-Optic Sensor with Temperature Compensation for PD Monitoring - Ghorat, Mohsen; Gharehpetian, Gevork B.; Latifi, Hamid; Hejazi, Maryam A.; Bagheri, Mehdi (MDPI, 2019)
This paper presented a new sensor to detect and localize partial discharge (PD) in power transformers based on a fiber Bragg grating (FBG). The fundamental characteristics of the proposed sensor, as a PD detector, were temperature compensation and direction independence. The proposed high-resolution PD detector operated based on the FBG wavelength shift. It is necessary to evaluate the physical parameters of the sensor to achieve the best results. Therefore, in this paper, the detected signal strength was investigated for different angles and temperatures. A Teflon hollow mandrel and two FBGs attached to the inner and outer surfaces of the hollow mandrel were chosen as the inner transformer PD detector. The changes in the sensor output were less than 0.4 mV and 0.5 mV for direction variations and a temperature variation of 14 °C (degrees Celsius), respectively. Consequently, the proposed sensor could be successfully employed for the detection of a transformer PD signal.
https://www.mdpi.com/1424-8220/19/23/5285
Keywords: partial discharge; fiber bragg grating; fiber optic sensor; acoustic wave; Research Subject Categories::TECHNOLOGY